Fundamental accounting principles - Wild, John J.; Chiappetta, Barbara; Shaw, Ken W. (New York : McGraw-Hill Irwin, 2011)
Covers changes in accounting, technology, and student learning styles. This title uses small business examples, integrates technology learning tools, and features pedagogical design
Includes index
Keywords: Accounting